Prevalence and characteristics of users of pre-exposure prophylaxis (PrEP) among men who have sex with men, San Francisco, 2014 in a cross-sectional survey: implications for disparities. (28th June 2016) - Snowden, Jonathan M; Chen, Yea-Hung; McFarland, Willi; Raymond, Henry F
Abstract : Objectives: Pre-exposure prophylaxis (PrEP) has gained a central role in prevention of HIV infection among men who have sex with men (MSM), particularly in San Francisco, California, USA. Programmes to enrol men in PrEP are being undertaken by a range of public and private organisations. PrEP will have the largest population impact if it reaches men who are most at risk for HIV infection, and is used in a manner that enables maximal efficacy. Access to PrEP also needs to be equitable. We report on the characteristics of men eligible for and using PrEP. Methods: Data were from the 2014 implementation of National HIV Behavioural Surveillance (NHBS) among MSM in San Francisco. NHBS uses venue-based sampling as the national standard for sampling MSM. We compare proportions of demographic characteristics of MSM using versus not using PrEP who are HIV-negative and meet Centers for Disease Control and Prevention guidelines to recommend PrEP. Results: Overall, 64.1% of HIV-negative MSM in San Francisco would meet guidelines for PrEP use, while 9.2% of MSM overall and 14.5% of MSM eligible were using PrEP as of 2014. Men using PrEP are more likely to be white and of older age. There were no differences between men using and not using PrEP in terms of education, income and health insurance. Conclusions: PrEP roll-out efforts should attempt to increase reach for young, black and Hispanic MSM. Failure to equitably provide access to PrEP could exacerbate the US disparity in new HIV infections for men of colour.